Effective field theory for spontaneously broken symmetry - Brauner, Tomáš (Lecture Notes in Physics, 2024)
This open access book is about spontaneous symmetry breaking, which is a classic area of theoretical physics that lies at the core of many fascinating phenomena such as ferromagnetism, superfluidity, superconductivity, or the Higgs mechanism. The book brings an up-to-date overview of spontaneous symmetry breaking and of modern effective field theory description thereof. The topics covered include the classification of Nambu–Goldstone bosons, nonlinear realization of internal and spacetime symmetries and the construction of the corresponding effective actions, and selected applications. With in-depth exposition of conceptual foundations and numerous illustrative examples, the book is accessible to anybody having taken a basic course on quantum field theory. It serves as a self-contained text for graduate students and junior researchers in diverse areas of physics, but also as a useful reference for experts.